Simultaneous solution for distribution of head in a two aquifer system - Eckhardt, John R., author; Sunada, Daniel K., advisor; McWhorter, David B., committee member; Longenbaugh, Robert A., committee member; Danielson, J. A., committee member (Colorado State University. Libraries, 1976)
A general computer program, WTSHED4, was developed to simulate the simultaneous areal distribution of head in a two aquifer system as a result of natural and artificial influences to each aquifer. WTSHED4 was constructed from a program developed by the professional groundwater staff at Colorado State University. The basic mathematic principal is to solve, by Gauss elimination technique, a two-dimensional form of the Boussinesq equation using an implicit central finite difference scheme. WTSHED4 is designed to simulate nonsteady-state conditions in a two-dimensional horizontal space including nonlinear flow conditions caused by a varying transmissivity. Physiographical influences such as impermeable, permeable and hydraulic boundaries are simulated without undue idealization. The hydrologic and geologic parameters which define a particular study area are incorporated into the model and can vary in both space and time. To check the validity of WTSHED4, five problems were modeled and results compared with analytic solutions. Agreement was very good, the only differences being a result of the time and space dimensions used in the finite difference approximation. Although WTSHED4 has been verified with several analytic solutions, it should be carefully used until additional laboratory or field verification is conducted.
Keywords: Aquifers -- Mathematical models